Adoption of lean tools to control delays in Malaysian construction projects - Ansha, Richard Hannis (2016)
The construction industry is a very significant sector in every economy worldwide. However, it is confirmed that high levels of delays exist in the construction industry around the world and this makes the situation in Malaysia more pervasive. In Malaysia, delays have been reported on several projects with some exceeding schedule for many days; some many years(s) and some delayed forever (total abandonment). While a variety of relevant models, methods, and approaches for minimizing delays have been contended, the application of lean thinking and tools in construction projects has been instrumental, thus, lean construction. Nonetheless, on the underlying idea of the lean concept, adequate prioritization and appropriate choice of lean tools is crucial for success or failure of its implementation. The objective of this research was to investigate delay sources in Malaysian construction projects and develop lean tool-delay control framework based on the impact of lean tools adoption. Based on the literature review, two main conceptual frameworks were developed and these are 41's and PESTLE Framework Analysis for the identified Internal and External delay sources respectively. In lieu of this, two main research models were developed. Meanwhile, forty lean tools were selected and ranked on each of the models. The research models were specified as an analytic hierarchy process (AHP) decision-based models, which was then tested through an interview in the Malaysian project context. The findings of the research model confirmed Last Planner System (LPS), Concurrent Engineering and Daily Huddle Meetings as the most effective lean-delay control tools for Model I (4Ps). Meanwhile, the least influenced lean tools were found to be Preventive Maintenance, SMART Goals, and Multi-Process Handling. Even so, Model II (PESTLE) found Concurrent Engineering, Last Planner System (LPS) and Daily Huddle Meetings as having a strong influence. However, Total Productive Maintenance (TPM), Preventive Maintenance and SMART Goals were found to be the least suitable lean tools for Model II. The research models showed internal consistency, rigor, and robust findings. Overall, the thesis has significant theoretical, methodological and practical implications. In general, the findings of this study would be feasible for knowledge and practice on delay control as it provides an important step and practical solutiohs through the adoption of the lean tool to control delays, especially in Malaysia.